2015
DOI: 10.1016/j.bone.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Bone and muscle: Interactions beyond mechanical

Abstract: The musculoskeletal system is significantly more complex than portrayed by traditional reductionist approaches that have focused on and studied the components of this system separately. While bone and skeletal muscle are the two largest tissues within this system, this system also includes tendons, ligaments, cartilage, joints and other connective tissue along with vascular and nervous tissue. Because the main function of this system is locomotion, the mechanical interaction among the major players of this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
224
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(242 citation statements)
references
References 75 publications
8
224
0
4
Order By: Relevance
“…Similarly, bone regeneration and increased risk of osteoporosis have been shown in NOD/scid-IL2Rγcnull animals, which exhibit defects in innate and adaptive immunity (Rapp et al, 2016), as well as in patients affected with acquired immunodeficiency syndrome (Annapoorna et al, 2004). Interestingly, the level of physical activity may also contribute to explain the loss of bone tissue across the three tumor models, especially keeping in mind that the interaction between skeletal muscle and bone tissue was initially described as mainly mechanical in nature (Brotto and Bonewald, 2015). Consistently, previous reports showed that the growth of colorectal tumors progressively affected the overall activity and physical performances in C26 hosts and Apc Min/+ mice (Baltgalvis et al, 2010; Toledo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, bone regeneration and increased risk of osteoporosis have been shown in NOD/scid-IL2Rγcnull animals, which exhibit defects in innate and adaptive immunity (Rapp et al, 2016), as well as in patients affected with acquired immunodeficiency syndrome (Annapoorna et al, 2004). Interestingly, the level of physical activity may also contribute to explain the loss of bone tissue across the three tumor models, especially keeping in mind that the interaction between skeletal muscle and bone tissue was initially described as mainly mechanical in nature (Brotto and Bonewald, 2015). Consistently, previous reports showed that the growth of colorectal tumors progressively affected the overall activity and physical performances in C26 hosts and Apc Min/+ mice (Baltgalvis et al, 2010; Toledo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The observed correlative changes in the bone quality and lean mass are related to the proposed endocrine interactions between bone and skeletal muscle mediated through osteoclast-producing or bone marrow mesenchymal cell-producing factors that have the anabolic effects in muscle 41 . Similarly, muscle can stimulate bone development through secretion of soluble myokines 42 . The present NHP study strongly suggests that caloric restriction is not feasible for treatment of osteoporosis in ADT patients 43 , and other approaches are needed to minimize this and other muscle-related or metabolic adverse effects of ADT.…”
Section: Discussionmentioning
confidence: 99%
“…Bone and muscle have an intimate relationship and show synchronization of tissue mass throughout life, from development to old age (Brotto and Bonewald, 2015). Exercise maintains or increases both bone and muscle mass, whereas disuse results in a reduction in mass/function of both tissues.…”
Section: Introductionmentioning
confidence: 99%